2017
DOI: 10.1371/journal.pone.0171088
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Genetic Structure and Signatures of Selection in Three Strains of Tanzania Shorthorn Zebu, Boran and Friesian Cattle by Genome-Wide SNP Analyses

Abstract: BackgroundMore than 90 percent of cattle in Tanzania belong to the indigenous Tanzania Short Horn Zebu (TSZ) population which has been classified into 12 strains based on historical evidence, morphological characteristics, and geographic distribution. However, specific genetic information of each TSZ population has been lacking and has caused difficulties in designing programs such as selection, crossbreeding, breed improvement or conservation. This study was designed to evaluate the genetic structure, assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 45 publications
2
32
2
Order By: Relevance
“…Studies of ROA in the genomes of ancient hominins [29][30][31] and early Europeans [32] have provided unique insights into the mating patterns and effective population sizes of our early forbearers. In non-humans, ROA patterns have provided insights into the differential histories of woolly mammoth [33], great ape [34,35], cat [36], canid [37][38][39][40][41][42], and bird [43] populations, while in livestock breeds they have provided insights into their origins, relationships, and recent management [42,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] and the lasting effects of artificial section [58,[61][62][63][64][65][66][67][68][69][70][71][72]…”
Section: Introductionmentioning
confidence: 99%
“…Studies of ROA in the genomes of ancient hominins [29][30][31] and early Europeans [32] have provided unique insights into the mating patterns and effective population sizes of our early forbearers. In non-humans, ROA patterns have provided insights into the differential histories of woolly mammoth [33], great ape [34,35], cat [36], canid [37][38][39][40][41][42], and bird [43] populations, while in livestock breeds they have provided insights into their origins, relationships, and recent management [42,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] and the lasting effects of artificial section [58,[61][62][63][64][65][66][67][68][69][70][71][72]…”
Section: Introductionmentioning
confidence: 99%
“…3 A larger percent of animals raised in Tanzania belong to the native populations which have been characterized to be low producers of meat, milk and eggs due to poor genetic potential. [4][5][6] For example, Tanzania Shorthorn Zebu (TSZ) animals which form 95% of all cattle and produce over 70% and 90% of milk and meat respectively are characterized by slow growth rates, low mature weight, long calving intervals, as well as low meat and milk yield. 1 Of the 16.7million goats about 98% belongs to the native Small East African (SEA) breed estimated to have low growth rates between 5 and 7g/day, small mature size ranging from 20 to 25kg and low carcass weights about 6 to 13kg.…”
Section: Introductionmentioning
confidence: 99%
“…Previous examples include characterization of TSZ using random amplified polymorphic DNA (RAPD) and microsatellite markers 4,51 as well as evaluation of genetic diversity in SEA goats using microsatellite DNA markers. 52 Recently Msalya et al 5 reported the genetic structure in three TSZ strains and Tanzanian Boran and Friesian breeds using genome-wide SNPs. 5 In the study, three indigenous strains of TSZ namely Sukuma, Tarime, and Maasai showed low genetic differentiation (F ST ) ranging from 0.011 to 0.013 among them (Table 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations